The Design of Resultant Force Vector Teaching AIDS For Senior High School Students - Subali, Bambang; Nikmah, Firda; Sumpono, Imam; Siswanto, Siswanto (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2019)
This study aims to create the design of resultant force vector teaching aids to improve students' conceptual understandings. The method of this study is the experimental method with Pretest-Posttest Control Group Design. The sample of this study is the tenth grade of 3 natural science class (X IPA 3) as the experimental class and the tenth grade of 4 natural science class (X IPA 4) as the control class at 1 Subah Senior High School. The vector teaching aids were tested for the validity by the validator using a questionnaire. The students' responses were measured using a questionnaire. The students' concept understandings were measured from the results of the pretest and posttest scores. The result of the teaching aids' feasibility test is 98.61%, showing that the teaching aids are very feasible to use. The increase of students' concept understandings measured by the students' learning outcomes in the experimental class after using the resultant force vector teaching aids is 0.7 included in the high category. The attitude and interest responses of the students after using the teaching aids get an average percentage of 71.06% included in the high category. Based on the research results, it is recommended for the teachers to utilize the environment to create real learning